"No Remorse, No Repent": Linking Lack of Remorse to Criminal Offending in a Sample of Serious Adolescent Offenders. (23rd February 2017) - Piquero, Alex R.
Abstract : Linking emotions to offender decision-making has only recently become of theoretical interest to criminologists, but empirical work in this area has not kept pace nor has such research examined the role of emotions to offending in offender-based samples. Recently, Warr outlined regret as one such emotion that may be useful in thinking about offending. Specifically, he argued that regret may be related to discontinuity in offending, or conversely that a lack of remorse may be related to continuity in offending. This paper uses data from a sample of serious adolescent offenders followed for seven years to investigate this hypothesis. Results provide support for Warr's hypothesis that remorse-resistant adolescents incur a higher number of re-arrests, while remorse-prone adolescents incur fewer re-arrests, even after controlling for other relevant risk factors.